Black lesbian identities, power and violence in public and private spaces - Stephens, Angeline V (Department of Psychology, 2019)
This study examined black South African lesbian’s lived experiences of power and violence through a reading of the lesbian body as a site through which social identities and power are produced, maintained, contested and reframed. The analytic gaze was cast inward on intimate relationships as well as outward on the social and community contexts. Forty black lesbian women who were or had been in intimate same-sex relationships participated in five focus group discussions and 22 depth interviews. Discourse analysis, edified by a feminist poststructuralist theoretical paradigm that advanced an intersectional analytical approach, revealed that participants assumed multiple and ambiguous gendered subject positions, and vacillated between positions of power and powerlessness in various contexts. The enactment of gendered and sexualised violence on the lesbian body within intimate lesbian relationships, as well as in public and social spaces that also marked politicised and racialised spaces, reflected tensions and contradictions that may be situated within the historical juxtapositioning of colonialism and democracy. While black lesbian women generally exercised high levels of self-surveillance in order to avoid culturally and socially endorsed raced and gendered practices that served to regulate and punish black lesbian sexuality; the lesbian body represented a powerful site of resistance in which gendered identities and sexualities were reconceptualised and renegotiated in more fluid ways within the current historical period in South Africa. Within this reframing, black lesbian identity represented and embodied a personal and a political statement of identity and resilience which troubled and contested citizenship in democratic South Africa. This study has foregrounded the importance of considering the interconnectedness of the public and private domains, and the intersections of history and contexts in the enactment and experience of power and violence in the lives of black lesbian women. It has important implications for research, programme design and policy.